Systems toxicology assessment of a representative e-liquid formulation using human primary bronchial epithelial cells. (2020) - Marescotti, Diego; Mathis, Carole; Belcastro, Vincenzo; Leroy, Patrice; Acali, Stefano; Martin, Florian; Dulize, Rémi; Bornand, David; Peric, Dariusz; Guedj, Emmanuel; Ortega Torres, Laura; Biasioli, Matteo; et al.
Graphical abstract: Highlights: A 3-step approach combining 1) real-time cytotoxicity, 2) high-content screening and 3) gene expression analysis was developed in NHBE cells. Different scoring methods were developed enabling a ranking based on cytotoxicity, phenotypic outcome, and molecular network perturbations. Flavoring substances that potentially contribute greatly to the overall mixture effect were identified (citronellol and alpha-pinene). Most of the cytotoxic effect appeared to be attributable to citronellol, with the remaining substances contributing due to synergistic effects. This case study underlines how testing both individual flavoring substances and mixtures are essential for a clear assessment of e-liquids. Abstract: The development of reduced-risk products aims to provide alternatives to cigarettes that present less risk of harm for adult smokers. Responsible use of flavoring substances in these products may fulfill an important role in product acceptance. While most flavoring substances used in such products are also used by the food industry and are considered safe when ingested, their impact when inhaled may require further assessment. To aid in such an assessment, a three-step approach combining real-time cellular analysis, phenotypic high-content screening assays, and gene expression analysis was developed and tested in normal human bronchial epithelial cells with 28 flavoring substances commonly used in e-liquid formulations, dissolved individually or as a mixture in a base solution composed of propylene glycol, vegetable glycerin, and 0.6% nicotine. By employing this approach, we identified individual flavoring substances that potentially contribute greatly to the overall mixture effect (citronellol and alpha-pinene). By assessing modified mixtures, we showed that, although cytotoxic effects were found when assessed individually, alpha-pinene did not contribute to the overall mixture cytotoxicity. Most of the cytotoxic effect appeared to be attributable to citronellol, with the remaining substances contributing due to synergistic effects. We developed and used different scoring methods (Tox-Score, Phenotypic Score, and Biological Impact Factor/Network Perturbation Amplitude), ultimately enabling a ranking based on cytotoxicity, phenotypic outcome, and molecular network perturbations. This case study highlights the benefits of testing both individual flavoring substances and mixtures for e-liquid flavor assessment and emphasized the importance of data sharing for the benefit of consumer safety.